2013
DOI: 10.1136/bmj.f1532
|View full text |Cite
|
Sign up to set email alerts
|

One year outcomes in patients with acute lung injury randomised to initial trophic or full enteral feeding: prospective follow-up of EDEN randomised trial

Abstract: Objective To evaluate the effect of initial low energy permissive underfeeding ("trophic feeding") versus full energy enteral feeding ("full feeding") on physical function and secondary outcomes in patients with acute lung injury. Design Prospective longitudinal follow-up evaluation of the NHLBI ARDS Clinical Trials Network's EDEN trialSetting 41hospitals in the United States.Participants 525 patients with acute lung injury.Interventions Randomised assignment to trophic or full feeding for up to six days; ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
215
1
16

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 244 publications
(245 citation statements)
references
References 55 publications
13
215
1
16
Order By: Relevance
“…Some evidence also suggests a lack of adverse consequences even with longer-term outcomes. A trophic/hypocaloric feeding trial of 525 patients, which instituted the most significant restrictions in enteral feeding (20% of caloric goal) for up to 6 days, found no differences in muscle strength, muscle mass, and 6-min walk test at 6 months or 1 year, although patients in the trophic/hypocaloric feeding group were more likely to be admitted to a rehabilitation facility during the first 12 months of follow-up [592]. The current evidence base would suggest that a trophic/hypocaloric or early full enteral feeding strategy is appropriate.…”
Section: We Suggest the Early Initiation Of Enteral Feedingmentioning
confidence: 99%
“…Some evidence also suggests a lack of adverse consequences even with longer-term outcomes. A trophic/hypocaloric feeding trial of 525 patients, which instituted the most significant restrictions in enteral feeding (20% of caloric goal) for up to 6 days, found no differences in muscle strength, muscle mass, and 6-min walk test at 6 months or 1 year, although patients in the trophic/hypocaloric feeding group were more likely to be admitted to a rehabilitation facility during the first 12 months of follow-up [592]. The current evidence base would suggest that a trophic/hypocaloric or early full enteral feeding strategy is appropriate.…”
Section: We Suggest the Early Initiation Of Enteral Feedingmentioning
confidence: 99%
“…Cognitive impairment, an outcome of vital importance to ARDS survivors and their caregivers (37), is common after ARDS (11,13,15,16). Emerging evidence suggests that mechanical ventilation per se may trigger neuronal apoptosis via vagal and dopaminergic pathways (36).…”
Section: Perspectivesmentioning
confidence: 99%
“…In survivors with cognitive impairment at 12 months, which constituted 55% of those examined, the average daily Pa O2 values (measured closest to 8:00 A.M.) were significantly lower compared with nonimpaired survivors (71 mm Hg [interquartile range, 67-80 mm Hg] vs. 86 mm Hg [interquartile range, 70-98 mm Hg]; P = 0.02) (13). In the most recent ARDSNet trial, long-term cognitive impairment was observed in 25% of survivors at 12 months (15,16). Compared PERSPECTIVES with prior trials (2, 3), the latest trial enrolled a greater proportion of subjects with mild ARDS (15,16).…”
Section: Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations